A new cycloartane-type triterpene and a new eicosanoic acid ester from fruits of Paullinia pinnata L. (March 2016) - Awouafack, Maurice D.; Ito, Takuya; Tane, Pierre; Kodama, Takeshi; Tanaka, Masami; Asakawa, Yoshinori; Morita, Hiroyuki
Graphical abstract: Highlights: The phytochemicals of a Cameroonian medicinal plant, Paullinia pinnata, were analyzed. A new cycloartane and a new eicosanoic acid ester were characterized by NMR and MS. The isolated compounds1 –7 and the MeOH extract were tested for antibacterial activity. Extract and cyclopinnatol (1 ) had significant and weak activities against Staphylococcus aureus . Abstract: A phytochemical study of the MeOH-soluble portion from the CH2 Cl2 /MeOH extract of the fruits of Paullinia pinnata resulted in the isolation of a new triterpenoid, cyclopinnatol (1 ), and a new eicosanoic acid ester, paulliniester (2 ), together with five known compounds including cycloart-22( E )-ene-3β, 25-diol (3 ), cycloartenol (4 ), β-sitosterol (5 ), betulonic acid (6 ) and oleanonic acid (7 ). The structures of the new compounds were elucidated by spectroscopic analyses (NMR and MS) and comparisons with published data. Cyclopinnatol (1 ) and the MeOH-soluble portion exhibited significant and weak antibacterial activities against Staphylococcus aureus, with MICs of 32 and 50 μg/mL, respectively.